Micro-nondestructive detection of the moisture and ion of rice seeds during germination under salt stress - Yang, Hongwei; Ji, Jianwei; Wang, Cheng; Zhang, Liying; Wang, Xiaodong; Song, Ping; Song, Peng (International Journal of Agricultural and Biological Engineering, 2019)
Salt stress is one of the major stress factors limiting rice productivity. Its damaging effects include water deficit due to osmotic stress, and ionic toxicity caused by ionic stress. It is very important to study the salt-tolerance mechanism of rice under salt stress, in order to improve the salt-tolerance capacity of rice and thereby increase the yield. In this experiment, the low field nuclear magnetic resonance (LF NMR) technique and the traditional dry-weight weighing method, the non-invasive micro-test technique (NMT) and the inductively coupled plasma emission spectrometry (ICP-AES) were applied to analyze the distribution of water and the flow of K+ and Na+ of rice seeds during germination under NaCl stress. The results suggested that for all different NaCl concentrations, as germination hours grew, the amplitude of NMR signals of the bound water that of the free water and the total amplitude all increased gradually. And the higher the NaCl concentration is, the weaker the increase trend is. In addition, the moisture content of the seeds and the total amplitude of NMR signals were positively correlated. The regression equation was y =191.53x +1463.6, the correlation coefficient was R=0.9823, and the determination coefficient was R2=0.9650. By this regression equation, the moisture content of each state of water during seed germination can be calculated. When without NaCl stress, the rice seeds absorbed K+ in the germination process. However, when under NaCl stress at different concentrations, K+ efflux was detected. The contents of K+ and K+/Na+ were lower than that under the control condition. The higher NaCl concentration is, the lower the K+ and K+/Na+ contents are. These results are in consistence with the K+ and Na+ contents detected by the inductively coupled technique. These empirical data offer a reference for the study of rice-seeds’ response mechanism under salt stress during germination and the screening of germplasm resources, and also put forward a new method of biopsy micro-nondestructive test for plants under stress.Keywords: nuclear magnetic resonance (NMR), non-invasive micro-test (NMT), NaCl stress, seed germination, moisture, dynamic ion flowDOI: 10.25165/j.ijabe.20191202.4245Citation: H W Yang, J W Ji, C Wang, L Y Zhang, X D Wang, P Song, et al. Micro-nondestructive detection of the moisture and ion of rice seeds during germination under salt stress. Int J Agric & Biol Eng, 2019; 12(2): 103–110.